Conceptualization of Religious Belonging of Christian Youth in Higher Education - Farooq, Amna; Sohail, Tayyaba (Journal of Islamic thought and civilization, 2019)
A phenomenological study was conducted to explore the lived experience of Christian students in HEC recognized private Higher Education Institutions (HEIs) to find out how the religious belonging of Christian youth influences their lives within their university. Qualitative research method was used for this study. Using phenomenology as the strategy of inquiry, in-depth interviews were conducted with a total of six participants including three girls and three boys currently studying in the University of Management and Technology (UMT), Lahore. The findings of the study revealed that the university did not ask the students about their religion, specifically. So, the students did not experience any discrimination at the time of admission. However, due to the lack of information about religious minority students, they were compelled to study Islamic studies as a subject. Due to their religious belonging Christian students experienced stereotypical behavior, such as some Christian students reported that their Muslim fellows avoided them and hesitated to share their meals with them after knowing their religious affiliation. Majority (4 out of 6) of the students did not experience any biased behavior from their teachers but some students did face biased behavior after revealing their religious affiliation. So, this study suggests that universities should ask students about their religious belonging and considering the needs of religious minority students, curriculum should seek input from religious minority groups. In order to promote religious tolerance at HEIs, universities should design curriculum for all students incorporating contents of interreligious harmony. Higher Education Commission (HEC) should ensure the implementation of policy regarding religious minorities at institutional level.